Intrinsic and extrinsic factors that influence consumers’ intention and purchase behavior: The case of eco-labeled dairy products - Herrera Gonzalez, Daniel Antonio (2020)
This research aims to undersatnd how intrinsic and extrinsic factors can influence consumers’ buying decision on shopping eco-labeled dairy products in order to close the gap between intention and purchase. This research is a quantitative study and uses the theory of reasoned action (TRA) of Ajzen & Fishbein (1980). Data were collected through surveys applied to consumers buying dairy products from a recognised dairy supermarket in Bogotá-Colombia. This work uses logistic regression as a statistical method to subsequently complement the analysis and enhance the results. It also uses exploratory factor analysis, confirmatory analysis, and a structural equation model. Findings show that ecological labels do not generate a positive influence to close the gap between intention and purchase. Manufacturers should strengthen environmental damage knowledge and awareness on dairy products consumption while keeping positive private benefits so that eco-labels really work and the gap between intention and purchase can be reduced.